DNA repair and erasure of 5-methylcytosine in vertebrates - Schomacher, Lars; Niehrs, Christof (Bioessays, 2017)
DNA methylation plays important roles in development and disease. Yet, only recently has the dynamic nature of this epigenetic mark via oxidation and DNA repair-mediated demethylation been recognized. A major conceptual challenge to the model that DNA methylation is reversible is the risk of genomic instability, which may come with widespread DNA repair activity. Here, we focus on recent advances in mechanisms of TET-TDG mediated demethylation and cellular strategies that avoid genomic instability. We highlight the recently discovered involvement of NEIL DNA glycosylases, which cooperate with TDG in oxidative demethylation to accelerate substrate turnover and promote the organized handover of harmful repair intermediates to maintain genome stability.